Mapping the Public-Private Partnership Researches in Waste Management: A Bibliometric Analysis - Ahmad Luthfi; Muhammad Faqih Naufal (Journal of Transformative Governance and Social Justice, 2023)
The increasing societal demands for effective waste management have compelled the government to provide optimal services in accordance with established standards, while carefully considering various relevant aspects. Public-Private Partnerships (PPP) have emerged as a conceptual framework to address these challenges. This article aims to comprehensively analyze and map the existing literature on public-private partnerships in the context of waste management. The mapping of this literature offers valuable insights into the theoretical foundations, practical implications, and potential future directions policy development in this field. Through bibliometric analysis and the application of the PICO Spider framework, a citation review was conducted based on the number of citations and journal sources. Co-authorship analysis was also performed based on authors and countries, while co-occurrence analysis was carried out based on all keywords. Furthermore, the analysis and visualization were conducted using the VOSviewer application. The utilization of VOSviewer facilitates the visualization of these findings, allowing for a more intuitive understanding and interpretation of the bibliometric analysis results. At the partnership level, the government needs to have full involvement, while higher-level government entities (such as provinces and central government) also play a role in indirectly supporting waste management programs. Private entities, on the other hand, can engage in waste processing using established technologies. However, if this is not feasible, privatization of waste management through independent Small and Medium Enterprises (SMEs) can serve as a new source of assistance for the government.